2018
DOI: 10.1177/0003319718772420
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prediabetes With Higher Coronary Atherosclerotic Burden Among Patients With First Diagnosed Acute Coronary Syndrome

Abstract: Diabetes mellitus (DM) is associated with more extensive coronary atherosclerosis and more vulnerable plaque phenotypes. However, DM should not be considered a homogeneous and purely binary entity in terms of risk assessment. We evaluated the impact of prediabetic status on coronary atherosclerosis burden in patients with first-time acute coronary syndrome (ACS) who underwent urgent coronary angiography. The patients were divided into DM, prediabetes, and control groups. The 3-vessel disease (TVD) rates and SY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 55 publications
5
41
0
2
Order By: Relevance
“…One hundred and seventy-seven patients were prediabetics constituting 24% of the study population. Similar prevalence of prediabetes was demonstrated among elective PCI patients and ACS patients in various registries [11,12]. Patients with prediabetes had the same age range as diabetics and normoglycemic subjects, yet female gender was more prevalent among the diabetic group.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…One hundred and seventy-seven patients were prediabetics constituting 24% of the study population. Similar prevalence of prediabetes was demonstrated among elective PCI patients and ACS patients in various registries [11,12]. Patients with prediabetes had the same age range as diabetics and normoglycemic subjects, yet female gender was more prevalent among the diabetic group.…”
Section: Discussionsupporting
confidence: 63%
“…Nakamura et al [18] demonstrated that among CAD patients, prediabetics and diabetics showed a higher prevalence of dyslipidemia, yet this was evident in postprandial lipid levels and not the fasting lipid levels which are used as the standard screening test. Similarly, Açar et al [12] found no difference in prevalence of dyslipidemia between prediabetic, normoglycemic, and diabetic subjects. The prevalence of CKD was not significantly different among the three groups, although diabetes is known as a common comorbid risk factor for CKD [19] as well as CKD pathophysiology starting in prediabetic subjects [20].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Most previous studies have shown that increased HbA 1c or FPG was signi cantly associated with poor in-hospital outcomes in patients with ACS and diabetes. An observational study that included 250 patients with ACS found that coronary atherosclerosis was more advanced in patients with HbA 1c ≥ 5.7% than in those with HbA 1c < 5.7% [17]. Goyal et al [25] conducted a post hoc analysis including two randomized controlled trials of acute myocardial infarction with STsegment elevation, involving 30,536 subjects with diabetes history, and showed that patients with inhospital glucose ≥ 144 mg/dL had a very high risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is the leading cause of morbidity and mortality in the industrialized world and diabetes mellitus (DM) magnifi es the risk of cardiovascular events. 1 Whereas "atherosclerosis" is a chronic and progressive process (causing stabile coronary artery disease, SCAD), the rupture of high-risk, vulnerable plaques is responsible for "atherothrombosis" (causing acute coronary syndrome, ACS). 2 Therefore, the presence of atherosclerosis is necessary but not suffi cient for atherothrombosis.…”
Section: Introductionmentioning
confidence: 99%